Diseño de un modelo de gestión por procesos para el área de la Red Publica Integral de Salud del Hospital Julius Doepfner del cantón Zamora, provincia Zamora Chinchipe, año 2013 - Martínez Romero, Jheimy Idelsa (2014)
Management Model was designed for processes for the area of Public Health Integrated Network “Julius Doepfner " Zamora canton Hospital, the same that is part of the " National Research Program: Designing a model for process management public or private organizations, 2012, " proposed by the Office of Graduate Studies of the Universidad Técnica Particular de Loja. As the proposed methodology by the IAT (Andaluz Institute of Technology) was taken. The description of the processes is made based on a flowchart and a tab process. Monitoring indicators and rethinking of improvement proposals were established. There are no clearly defined processes and the roles and functions of personnel working in the area; therefore, there are weaknesses in the activities currently being developed. That the area of Public Health Network Comprehensive better approach to public service, inspired by the objectives of the National Plan for Good Living for results and.